Real-time simultaneous detection of volcanic Hg and SO₂ at La Fossa Crater, Vulcano (Aeolian Islands, Sicily) - Aiuppa, A; Bagnato, E; Witt, M; Mather, T; Parello, F; Pyle, D; Martin, R (American Geophysical Union, 2007)
Measuring Hg/SO₂ ratios in volcanic emissions is essential for better apportioning the volcanic contribution to the global Hg atmospheric cycle. Here, we report the first real-time simultaneous measurement of Hg and SO₂ in a volcanic plume, based on Lumex and MultiGAS techniques, respectively. We demonstrate that the use of these novel techniques allows the measurements of Hg/SO₂ ratios with a far better time resolution than possible with more conventional methods. The Hg/SO₂ ratio in the plume of FO fumarole on La Fossa Crater, Vulcano Island spanned an order of magnitude over a 30 minute monitoring period, but was on average in qualitative agreement with the Hg/SO₂ ratio directly measured in the fumarole (mean plume and fumarole ratios being 1.09 x 10⁻⁶ and 2.9 x 10⁻⁶, respectively). The factor 2 difference between plume and fumerole compositions provides evidence for fast Hg chemical processing the plume.